A Study on Impact of Age and Years of Experience on Job Satisfaction of Doctors - Khanna, Monika; Henry, D. (SFIMAR Research Review, 2021)
Doctors are in a profession where they have to work without any time limitations and under very stressful circumstances, but they are expected to maintain their cool under all conditions and perform in the best possible manner. These doctors have to live up to the competition as well as maintain the standards of their treatment and care. The present paper is an attempt to find if age and experience has any impact on their job satisfaction. A structured questionnaire was administered and the survey was taken by doctors of different hospitals and a total of 150 responses were analysed. The results show that there is significant variation in job satisfaction with age and experience.